Recent methods in the production of activated carbon from date palm residues for the adsorption of textile dyes: A review - Alharbi, Hattan A.; Hameed, Bassim H.; Alotaibi, Khaled D.; Al-Oud, Saud S.; Al-Modaihsh, Abdullah S. (Frontiers in Environmental Science, 2022)
Textile dyes are organic compounds that can pose an environmental threat if not properly treated. They can cause many problems ranging from human health, ecosystem disturbances and the reduction of the aesthetic value of the water bodies. Adsorption process using activated carbon (AC) has been proven to be effective in treating dyes wastewater. However, production of AC is limited by the non-renewables and relatively expensive precursor of coals. Date palm residues (DPR) provide a good alternative for AC’s precursor due to their continuous supply and abundancy in addition to possessing good physiochemical properties such as high oxygen element and fixed carbon. This paper provides a review on the potential of date palm residues as AC in adsorbing textile dyes and the recent technological advances adopted by researchers in producing DPR-based AC. This paper presents the background review on date palm, textile dyes, biochar and AC, followed by production methods of AC. Isotherm and kinetic models employed in literature are also discussed, together with the explanation of parameters accompanied by these models. Conversion of DPR into AC was noticed to be more efficient with the advancement of activation methods over the years.